Padrões de ambientes e comunidades vegetais em área degradada por erosão no Cerrado - Campos, Maria Lúcia Furtado Coelho (2019)
There are many areas with degraded soils by erosion in the region known how Triângulo Mineiro. The soil degradation brings incontable social and environmental negative consequences, such less productive capacity from agricultural, slope collapses, stream, weir and rivers siltings. An efficient solution to recovery the degraded areas is revegetation. To understand the dinamics of natural revegetation inside disturbed environments is the first step to manage and guide the recovery of degraded areas. To do that, this study intend contribute with new information about fittest flora species to natural regeneration inside an area completely degraded as well its recomposion process. The scope is phytosociological studies and its soil relations to understand and stablish patterns from selected field. To phytosociological studies 4 areas were sampled inside the same microbasin (“cerradão”, “mata”, “voçoroca mata” and “voçoroca cerradão” areas), distributed portions of 10 x 10 m in each area, on total from 39. Were collected all individuals with circunference ≥ 10 cm, measured 30 cm from the soil. Inside the larger portion, sub portions of 5 x 5 cm were installed, where the individuals with circunference ≥ 5 and < 10 cm from 30 cm of the soil were sampled. Inside the 10 x 10 m portions were also installed 2 x 2 m sub portions to the sampling of the individuals with < 5 cm of circunference. For the purposes of quantitative studies about the relation soil – vegetation, in each portion were collected deformed and non deformed soil samples in 0 to 20 cm depth. To verify the pedological variations were opened profiles. The physical and chemical analisys were done to classify the soils and the plants were identified and mensured (height and diameter). The study was developed int three chapiters. In the first one was realized the soil/substract caracterization from each area. In the second the phytosociological structure was avaliated. And in the third was realized the relationship betwen vegetation and species abundance with physical-chemical soil properties.